An international, cross-sectional survey of psychiatry researchers and clinicians: perceptions of complementary, alternative, and integrative medicine - Ng, Jeremy Y.; Kochhar, Jassimar; Cramer, Holger (Frontiers in Psychiatry, 2024)
Background Psychiatry is a branch of medicine that focuses on mental, behavioral and emotional well-being. Complementary, alternative, and integrative medicine has been an increasingly popular choice for patients with psychiatric disorders, therefore our study aimed to explore the perceptions of psychiatry researchers and clinicians on the use of CAIM. Methods We conducted an online, anonymous, cross-sectional survey for researchers and clinicians who have published their work in psychiatry medical journals that are indexed in MEDLINE. 42,667 researchers and clinicians were sent the link to the survey after extraction of their email addresses from their respective publications. Respondents were asked numerous multiple-choice questions regarding their perceptions on various CAIM therapies, followed by an open-ended question where they could include any additional thoughts. Results The survey was completed by 987 respondents, with a majority identifying as a researcher (n=447, 46.51%), or as both a researcher and a clinician (n=368, 38.29%) within the field of psychiatry. Most respondents (n=629, 78.04%) perceived mind-body therapies such as meditation, biofeedback, hypnosis, and yoga to be the most promising CAIM therapy for the prevention, treatment, and management of psychiatric diseases. Many participants said that they agree (n=285, 38.14%) that most CAIM therapies in general are safe, however, many disagree that CAIM therapies are effective (n=245, 32.93%). Respondents indicated that there is value to conducting research on CAIM therapies (n=356, 47.91%), and that there should be more funding allocated to researching these therapies (n=265, 35.71%). Respondents were also in agreement that clinicians should receive training on CAIM therapies through formal education (n=295, 39.76%) or supplementary education (n=380, 51.28%). Conclusion The findings from this study showed that there is great interest and potential in researching CAIM within the field of psychiatry. This information can be used as a basis for further research and to develop tailored educational resources for researchers and clinicians in psychiatry.